Implementation of Problem-Based Learning (PBL) Model Integrated with Augmented Reality to Improve Learning Outcomes of Class XI MAN 2 Tidore Kepulauan on Uniform Linear Motion Material - Rosdiana S Syahman; Mardia Hi Rahman; Hutri Handayani Isra (Eduvest - Journal of Universal Studies, 2026)
This research investigates the effect of integrating the Problem-Based Learning (PBL) model with Augmented Reality (AR) in improving student learning outcomes in physics, specifically in the material of Regular Straight Motion (GLB). Conducted at MAN 2 Tidore Islands, the study involved grade XI students during the odd semester of the 2025/2026 school year. Using a quantitative approach with a Pretest-Posttest Control Group Design, the results showed significant improvements in the experimental group. The average final score of the experimental class was 62.46, while the control class scored 40.23, with a p-value of 0.005 (< 0.05), confirming that AR-based PBL effectively enhanced learning outcomes. The N-Gain analysis revealed a 73.35% improvement in the experimental class, categorized as quite effective, compared to 24.58% in the control class. The integration of AR provided interactive, engaging, and accessible visualizations of abstract concepts, fostering better understanding and active student involvement. This study highlights the potential of AR-assisted PBL as an innovative teaching strategy to improve the quality of physics learning and suggests further exploration of this model in other educational contexts.